Variables asociadas a infección del tracto urinario en pacientes con catéter urinario permanente años 2018 - 2021 Hospital Regional de Loreto Iquitos 2023 - Escobedo Vela, Almendra Thalia (2024)
The objective of this research is to determine the variables that are associated with the time of presentation of urinary tract infection in patients with indwelling urinary catheter years 2018-2021 Hospital Regional de Loreto Iquitos 2023. The method was quantitative, and the design was non-experimental. Descriptive, correlational, retrospective. The population and sample were made up of 68 medical records of patients who presented urinary tract infection with an indwelling urinary catheter. The technique was a documentary review and the instrument was a record of variables and identification of the time of presentation of the urinary tract infection in patients with an indwelling urinary catheter. The results obtained were: 41.2% were between 30 and 59 years old, 73.53% were male, 76.6 %were hospitalized in the Intensive Care Unit, and the most frequent microorganism was Pseudomonas aeruginosas. with 30.9%, followed by Escherichia coli with 23.52%. Regarding the time of presentation of urinary tract infection with an indwelling urinary catheter, it was from 7 days to more with 72.06%. When establishing an association between the variables, an association was found with age with p= 0.002, sex p= 0.038 and hospital service p= 0.026, no association was found with the type of microorganism with p= 0.3671. In conclusion, there is a significant statistical association with the time of presentation of urinary infection in patients with an indwelling urinary catheter, age, sex and hospital service, so it is essential to take into account compliance with biosafety standards when establishing a indwelling urinary catheter taking into account the age, sex of the patient and hospital service.